2023
DOI: 10.1007/s00432-023-04700-7
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNAs enable precise diagnosis and prediction of early relapse after nephrectomy in patients with renal cell carcinoma

Abstract: Purpose Renal cell carcinoma belongs among the deadliest malignancies despite great progress in therapy and accessibility of primary care. One of the main unmet medical needs remains the possibility of early diagnosis before the tumor dissemination and prediction of early relapse and disease progression after a successful nephrectomy. In our study, we aimed to identify novel diagnostic and prognostic biomarkers using next-generation sequencing on a novel cohort of RCC patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…lncRNAs were proven to play an integral role in the pathogenesis of allergic disease by regulating the differentiation and apoptosis of hematopoietic stem cells, bone marrow cells, and the activation of monocytes, macrophages, and dendritic cells in immune regulation ( Cheng et al, 2022 ). ZNF667-AS1 has been the focus of recent research on inflammatory conditions and cancer with an emphasis on its function in the control of inflammatory pathways ( Di Fiore et al, 2021 ; Zheng et al, 2021 ; Fan et al, 2022 ; Luan et al, 2022 ; Ma et al, 2022 ; Bohosova et al, 2023 ). Excitingly, we discovered that Liu et al's bioinformatics study ( Liu et al, 2019 ), based on data GSE67472, identified ZNF667-AS1 as an important gene involved in the pathogenesis of asthma, which is also downregulated in asthma.…”
Section: Discussionmentioning
confidence: 99%
“…lncRNAs were proven to play an integral role in the pathogenesis of allergic disease by regulating the differentiation and apoptosis of hematopoietic stem cells, bone marrow cells, and the activation of monocytes, macrophages, and dendritic cells in immune regulation ( Cheng et al, 2022 ). ZNF667-AS1 has been the focus of recent research on inflammatory conditions and cancer with an emphasis on its function in the control of inflammatory pathways ( Di Fiore et al, 2021 ; Zheng et al, 2021 ; Fan et al, 2022 ; Luan et al, 2022 ; Ma et al, 2022 ; Bohosova et al, 2023 ). Excitingly, we discovered that Liu et al's bioinformatics study ( Liu et al, 2019 ), based on data GSE67472, identified ZNF667-AS1 as an important gene involved in the pathogenesis of asthma, which is also downregulated in asthma.…”
Section: Discussionmentioning
confidence: 99%